Educational Demonstration of Eye Exercises Video Based Affected Knowledge, Anxiety, Self-Resilience of Cataract Patients - Lie liana Fuadiati; Desy Rinawaty; Nadhifah Rahmawati; Afiatur Rohimah (Journal of Ners and Midwifery, 2025)
Cataracts are the main cause of blindness throughout the world which can actually be prevented. Lack of knowledge, increased anxiety and lack of self-resilience in cataract patients cause patients to be afraid to seek treatment from health services. The research design used Quasi Experimental Pre-Post Test with One Group Design. The sample in this research was 42 cataract patients. The instrument for this research was the Knowledge, Anxiety and Self-Resilience Questionnaire. Data analysis in this research used the Wilcoxon Test statistical test. The results of the Wilcoxon Test of knowledge in the experimental group showed that Sig. equal to 0.000 or <0.05 (error level), meant that there was a difference in knowledge results before and after treatment. Meanwhile, the results of the Wilcoxon test for anxiety in the experimental group showed that Sig. equal to 0.008 or <0.05 (error level), it could be concluded that there was a difference in anxiety results before and after treatment. And the results of the Wilcoxon Test of self-reliance in the experimental group showed that Sig. equal to 0.000 or <0.05 (error level), meant that there was a difference in the results of self-resilience before and after being given treatment. Video-based Educational Demonstration Of Eye Exercises is effective for increasing knowledge, reducing anxiety and increasing self-resilience in cataract patients. Health workers can increase knowledge about cataracts and non-pharmacological therapy independently to increase personal resilience and reduce anxiety in cataract patients, as an effort to improve optimal health services.